Development and Validation of the Cell-based Functional Method for Neutralizing Anti-adalimumab Antibodies Detection in Human Serum - M. A. Nikiforova; I. A. Valouev; A. V. Petrov; E. E. Beketov; I. E. Shokhin (Разработка и регистрация лекарственных средств, 2024)
Introduction. Adalimumab, a fully humanized monoclonal antibody, is a tumor necrosis factor (TNFα) inactivator that is used against a number of autoimmune diseases such as rheumatoid arthritis and other most common inflammatory arthropathies (ankylosing spondylitis, psoriatic arthritis). Despite the proven efficacy of adalimumab treatment, there is a risk of adverse events, tied up with the formation of anti-drug antibodies, including neutralizing antibodies. Currently, the evaluation and characterization of neutralizing antibodies has become an important part of clinical trials in the development of new drugs and biosimilars.Aim. The aim of this study is to develop and validate the cell-based functional method for neutralizing anti-adalimumab antibodies determination in human serum.Materials and methods. For determination of neutralizing anti-adalimumab antibodies, the cell line L-929 has been employed. L-929 is a cell line sensitive to the TNFα-mediated apoptosis; the neutralizing antibodies interact with adalimumab that leads to TNFα-mediated cytotoxicity. Cytotoxicity was measured using resazurin, an aromatic compound that is a redox indicator.Results and discussion. The developed method was validated for cut point, selectivity, sensitivity, precision, specificity and stability (short- and long-term). An important part of a method development for determining neutralizing antibodies is the selection of concentrations of TNFα (4 ng/ml) and adalimumab (250 ng/ml), as well as determining the minimum required dilution – this parameter is established as 1 : 20. Cut point was chosen as a «floating» cut point, and a correction factor (normalization factor) was determined equal to 0,86. The sensitivity of the developed method was estimated at 108,9 ng/ml of neutralizing anti-adalimumab antibodies.Conclusion. The obtained results can be applied for determining anti-adalimumab neutralizing antibodies in the assessment of the adalimumab immunogenicity, including clinical trials.